2022
DOI: 10.1111/jfpp.16875
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin‐rich, erucic acid‐lean nutraceutical supplements by microwave‐assisted solvent extraction of brown and yellow mustard seeds

Abstract: The seeds of brown mustard-Brassica juncea (BJ) and yellow mustard-Brassica campestris (BC) are principally valued as sources of edible oil and also as condiments. Additionally, the seeds are an important source of antioxidant melatonin (MT) which reportedly has significant anti-cancer, hypoglycaemic (Paul et al., 2021), and hypocholesterolemic properties (Chakraborty & Bhattacharjee, 2017; Li et al., 2017). However, consumption of whole seeds of BJ and BC for the realization of the benefits of the aforementio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Mohamed et al [121] observed an improvement in oil quality of rapeseed cultivars due to the priming of Brassica napus L. seeds with MT, which increased the concentration of unsaturated fatty acids like linolenic and oleic acids with reduced glucosinolates and saturated fatty acids such as palmitic and arachidic acids under salinity stress. The application of MT improved yield-related characteristics such as seed yield per plant, 1000 seed weight, seed oil content, and seed yield in mustard [122]. Wang et al [123] investigated the impact of MT on yield traits of soybean and reported an increased number of pods, seeds per pod, and grain yield under stress.…”
Section: Melatonin's Role In Crop Yield and Qualitymentioning
confidence: 99%
“…Mohamed et al [121] observed an improvement in oil quality of rapeseed cultivars due to the priming of Brassica napus L. seeds with MT, which increased the concentration of unsaturated fatty acids like linolenic and oleic acids with reduced glucosinolates and saturated fatty acids such as palmitic and arachidic acids under salinity stress. The application of MT improved yield-related characteristics such as seed yield per plant, 1000 seed weight, seed oil content, and seed yield in mustard [122]. Wang et al [123] investigated the impact of MT on yield traits of soybean and reported an increased number of pods, seeds per pod, and grain yield under stress.…”
Section: Melatonin's Role In Crop Yield and Qualitymentioning
confidence: 99%
“…Therefore, as a reminder and encouragement, this type of vegetable was involved in this study. Mustard contains many essential nutritional and medicinal components, as it is an important source of glucosides and omega-3 fatty acids [16]. These two compounds are known for their importance for health, especially in controlling inflammation and some heart diseases.…”
Section: Introductionmentioning
confidence: 99%